Allele 4G of gene PAI-1 associated with prothrombin mutation G20210A increases the risk for venous thrombosis - Barcellona, Doris; Fenu, Lara; Cauli, Cristiana; Pisu, Giulia; Marongiu, Francesco (Thrombosis and Haemostasis, 2003)
Several studies have tried to clarify the role of polymorphism 4G/5G of the PAI-1 gene in venous thromboembolism without reaching any final conclusion. It has been demonstrated that this polymorphism may induce an increased risk for venous thromboembolism (VTE) in patients with thrombophilic defects. We studied the association of prothrombin mutation G20210A with 4G/5G polymorphism in 402 VTE patients and 466 healthy controls. Patients affected by prothrombin mutation G20210A, with or without the concomitant presence of allele 4G, had a 3.7 thrombotic risk (C.I. 95% 2.3–6.0; p<0.0001). Moreover, genotype 4G/4G is a mild risk factor for VTE, irrespectively of whether the prothrombin mutation was present.Logistic regression analysis showed that patients carrying the G20210A prothrombin mutation with allele 4G gave an odds ratio for VTE of 6.1 (C.I. 95% 3.2 – 11.4; p<0.001). The risk increased up to 13.0 (C.I. 95% 3.0 – 60.4; p<0.001) when we considered the association of the prothrombin mutation with genotype 4G/4G. The G20210A mutation without allele 4G (5G/5G) was not a risk factor for VTE. In conclusion, we believe that patients affected by VTE with concomitant presence of the G20210A prothrombin mutation could be tested for genotype 4G/4G to better define their thrombotic risk.
Keywords: Deep vein thrombosis; 4G/5G polymorphism of PAI-1 gene; G20210A prothrombin mutation